(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper's objectives are to evaluate the applicability of current international instruments to combat cybercrime in light of artificial intelligence (AI) technologies and to offer a brief overview of ongoing international organizations’ policy initiatives that could soon have a significant influence on the development of cybercrime legislation. This essay addresses the implications that developing AI policies might have for managing the criminal justice system, particularly with regard to combating cybercrimes. Deep fakes and other contemporary developments in the usage of AI apps and systems to carry out destructive and unlawful actions are examined. The report concludes with a suggestion for a different approach to developing efficient policy solutions to stop cybercrime using AI systems. Over the last decade, cyber threats have become a challenge for the proficient. Current security systems need more advancement to deal with exceptionally trained cybercriminals. Implementing Artificial Intelligence (AI) techniques helps detect scams but may bring other risks. This research paper focuses on the intersection between cyber security threats and their forestallment using Artificial Intelligence (AI) technologies. It briefly outlines Artificial Intelligence (AI) applications for several cybersecurity crimes and estimates the probability of expanding cybersecurity by conservation of the defense mechanisms. The innovation of Artificial Intelligence has unlocked new room for the world’s future. The methods to secure data have influenced the growth of Artificial Intelligence (AI) in cybersecurity. The paper aims to establish awareness regarding the benefits of Artificial Intelligence (AI) technology and its assistance in protecting on a larger scale, i.e., in an organization or a business. The statistics mentioned in the paper are taken from valid sources and proved to favor the study. This study assesses the potential for increasing cybersecurity capabilities by strengthening the defensive mechanism and offers a succinct summary of artificial intelligence (AI) implementations of various cybersecurity employing artificial technologies. After reviewing the state-of-the-art artificial intelligence cybersecurity software, we may deduce that useful applications already exist. First and foremost, they deploy neural networks to safeguard several other cybersecurity domains as well as the peripheral. However, it was evident that the effective resolution of some cybersecurity issues would need the application of artificial intelligence techniques. For instance, detailed information is crucial for making strategic decisions, and one of the unresolved cybersecurity challenges is the need for logical decision support.